Comparison of detergent and CTAB method for isolation of DNA from Salak ( Salacca zalacca (Gaert.) Voss. ‘Pondoh’) - Arfa, Namira Nur; Daryono, Budi Setiadi; Reflinur, Reflinur (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2018)
This study conducted in Laboratory of Molecular Biology, Balai Besar Bioteknologi dan Sumberdaya Genetik Pertanian (BB- Biogen) Bogor. The aims of this study are to determine and comparing the quantity,Ã‚Â quality and the efficiency of DNA isolation result using detergent method and CTAB method.Ã‚Â The parameters observed in this study are the value of DNA concentration, purity, and visualization result using gel electrophoresis. The samples are the leaves of Salak Ã¢â‚¬ËœPondohÃ¢â‚¬â„¢ (Salacca zalacca (Gaert.) Voss.). Detergent method is a method which was developed by Faculty of Biology UGM, it has simple method and relatively affordable cost. Meanwhile, CTAB method is one of the commonly used methods of DNA isolation protocol with relatively expensive cost.Ã‚Â Detergent method used detergent in the cell wall separation and protein removal in the sample. The CTAB method used Cetyltrimethyl ammonium bromide (CTAB) for cell membrane separation in the sample. The research methods included DNA isolation with detergent and CTAB methods, PCR analysis and electrophoresis. Data analysis was done quantitatively Ã‚Â using spectrophotometric method and qualitative used electrophoresis method. The result of the study Ã‚Â showed that DNA isolation usingÃ‚Â CTAB method showed higher purity compared with detergent method with the purity values ranging from 1,3- 1,4 . Meanwhile, the concentration of DNA in the detergent method was higher than that of CTAB with the highest concentration of 1730 Ã‚Âµg/ml. There is no difference between theÃ‚Â quality of genomic DNA isolated by CTAB and detergent methods.